2010
DOI: 10.3109/08860220903377597
|View full text |Cite
|
Sign up to set email alerts
|

Common Genetic Variants in the Chromogranin A Promoter Are Associated with Renal Injury in IGA Nephropathy Patients with Malignant Hypertension

Abstract: The present study aimed to investigate whether genetic variants in the chromogranin A (CHGA) promoter were associated with malignant hypertension (MHT) and renal functional damage. The polymorphisms of CHGA promoter in 39 patients with malignant hypertension secondary to idiopathic IgA nephropathy (IgAN-MHT), 23 patients with primary malignant hypertension and 63 controls were genotyped by sequencing. Four diploid genotypes with minor allele frequencies of approximately ≥10% for individual CHGA SNP loci or hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…11 A recent report also indicates that CHGA genetic variation predicts renal injury in IgA nephropathy with malignant hypertension in China. 13 In this study, we explore potential functional motifs in the CHGA 39-untranslated region (39-UTR) and identify a partial motif match between microRNA (miR) hsa-miR-107 and the common CHGA 39-UTR variant C+87T (rs7610), with a superior match for the risk allele +87T. We then investigate whether this motif match regulates CHGA expression using a variety of techniques, proceeding ultimately to in vivo effects on control of BP in the humanized CHGA transgenic mouse.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…11 A recent report also indicates that CHGA genetic variation predicts renal injury in IgA nephropathy with malignant hypertension in China. 13 In this study, we explore potential functional motifs in the CHGA 39-untranslated region (39-UTR) and identify a partial motif match between microRNA (miR) hsa-miR-107 and the common CHGA 39-UTR variant C+87T (rs7610), with a superior match for the risk allele +87T. We then investigate whether this motif match regulates CHGA expression using a variety of techniques, proceeding ultimately to in vivo effects on control of BP in the humanized CHGA transgenic mouse.…”
Section: +mentioning
confidence: 99%
“…17 In a biogeographically broader arena, genetic variation at the CHGA locus was associated with renal injury in Chinese patients with IgA nephropathy and malignant hypertension. 13 In the glomerulus, CHGA itself triggers profibrotic responses in cultured glomerular capillary endothelial and mesangial cells. 12 Here, we provide evidence of the functionality of the CHGA 39-UTR variant and its differential interaction with a specific miR.…”
Section: Overview: Chga In Hypertension and Nephropathymentioning
confidence: 99%
“…Epidemiological studies have demonstrated an excessive risk of CKD progression to ESRD among African Americans, even after controlling for confounding factors [20,21]. In this population, several potential disease-susceptibility loci and gene polymorphisms for hypertensive-CKD leading to ESRD have been identified including CHGA, the adrenergic catecholamine storage protein [8][9][10][22][23][24][25]. This study supports observations in humans that loss of kidney function leads to build-up of plasma CHGA and triggers mesangial cell activation via scavenger receptor, mounting an oxidative stress response potentiating inflammation and fibrosis ensuing in the disease phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship has been established between CHGA, hypertension and kidney disease. Kidney dysfunction contributes to increasing levels of plasma CHGA [4,5] and several CHGA gene polymorphisms contributing to traits of autonomic blood pressure control, hypertension, and hypertensive kidney disease have been identified [6][7][8][9][10]. In the African American Study of Kidney Disease and Hypertension (AASK) cohort, glomerular filtration rate (GFR) decline in CKD was associated with a polygenic trait with contributions from several genes involved in catecholamine biosynthesis, storage and catabolism including CHGA [8].…”
Section: Introductionmentioning
confidence: 99%
“…Lillie [15] ve arkadaşları, Salem [16] ve arkadaşları, Chen [13] ve arkadaşlarının çalışmalarında da bizim çalışmamızda olduğu gibi C-415T polimorfik bölgesinde en sık T alleli ve genotip olarak da TT genotipi saptanmıştır. Yu [17] ve arkadaşlarının 23'ü primer malign hipertansiyon hastası, 39'u IgA nefropatisine sekonder malign hipertansiyon hastası ve 63'ü sağlıklı kontrol grubundan oluşan toplam 125 kişi ile yaptıkları bir başka çalışmada ise CHGA promotor bölgesinde yaygın olarak görülen polimorfizmler incelenmiş ve C-415T bölgesi için TT genotipi taşıyanların TC ve CC genotipine sahip bireylerden daha yüksek serum kreatinin değerlerine sahip oldukları gösterilmiştir. CHGA promotor bölgesinde yaygın görülen polimorfizmlerin ve haplotiplerin malign hipertansiyonun başlangıcında etkili olmayabilecekleri ancak IgA nefropatisine sekonder malign hipertansiyonda renal disfonksiyondan sorumlu olabilecekleri ileri sürülmüştür.…”
Section: Discussionunclassified